Role of Gut Microbiota in the Production and Regulation of Serotonin Biosynthesis in the Gastrointestinal Tract - Abubaker, Sarah (Université d'Ottawa / University of Ottawa, 2025)
The gut microbiota, a complex ecosystem of microorganisms residing in the gastrointestinal tract, involved in the regulation of numerous physiological processes, including neurotransmitter synthesis. Among these, serotonin (5-hydroxytryptamine; 5-HT) a key neuromodulator has gained significant attention due to its dual regulation of both the enteric and central nervous systems. In the gastrointestinal tract, approximately 90% of the body's serotonin is synthesized by enterochromaffin cells, with gut bacteria significantly influencing this process through microbial metabolism of amino acid L- tryptophan. This thesis aims to investigate the role of gut microbiota in serotonin synthesis, focusing on its mechanistic contributions and regulatory pathways. A key regulatory mechanism involves the rate-limiting enzyme tryptophan hydroxylase (TPH), which facilitates the conversion of tryptophan into 5-hydroxytryptophan (5-HTP), a crucial serotonin precursor. To explore gut microbial contributions, eighty-two bacterial isolates and reference strains were screened for TPH activity, with nine strains further assessed for 5-HTP synthesis. Two strains were then identified and evaluated for their capacity to produce 5-HT, induce host cell responses, and exhibit probiotic properties. Our findings demonstrated that the gut microbiome exerts a diverse influence on serotonin synthesis, with certain microbial communities acting as more potent producers of 5-HTP than others, highlighting their potential role in serotonergic regulation and therapeutic applications.
Keywords: gut microbiota; serotonin synthesis; enterochromaffin cells; tryptophan hydroxylase; gut-brain axis; microbial metabolites